A Guideline for English Articles System Investigating Students of the English Department Understanding of the Articles System in English (مجلة العلوم الشاملة, 2024)
Articles is an important area of English language learning and teaching. This study discusses students understanding of the articles system in English through investigating and analyzing the answers of students to an exercise. A qualitative and quantitiveapproach of investigation was employed and the data of this study was collected from the answers of students of the English Language Department in the Faculty of Arts Aljmail to a written task about articles. The finding revealed that students lack of full understanding and enough knowledge of how English articles system works seems to be obvious. Students answers seems to be based on memorization of articles rules rather than based on understanding the context in which the article is used or required. However, in some incidents and with a number of students there are evidence of good use and correct choice of articles. Teachers should be aware of the significance of teaching this area of English language and allocate enough time and appropriate teaching methodologies to ensure better understanding and pay more attention to the context than to memorization of rules.